Competitive interactions under experimental conditions affect diel feeding of two common aquaculture fish species Labeo calbasu (Hamilton, 1822) and Cirrhinus cirrhosus (Bloch, 1795) of southern Asia - Rahman, Mohammad Mustafizur; Balcombe, Stephen Richard (Wiley-Blackwell Publishing Ltd, 2017)
The effects of interspecific competition on grazing between two important aquaculture species, mrigal carp Cirrhinus cirrhosis and orangefin labeo Labeo calbasu, in single and in dual combinations were observed in experimental tanks. This study demonstrated that the presence of a competitor did not cause C. cirrhosis to shift its diel feeding patterns. That said, both total food intake and food preference were negatively affected in C. cirrhosis by the presence of a superior competitor, L. calbasu. The feeding patterns of L. calbasu became diurnal in the presence of C. cirrhosus, suggesting highly complex competitive interactions between the two species. That L. calbasu was specifically able to shift circadian feeding patterns to maximize energy intake in the presence of a competitor would suggest that it would be a suitable species to stock in a mixed species aquaculture system.